Movement Teacher - Lusinta Rehna Ginting, Fachruddin Azmi, (The Islamic Education and Multiculturalism Foundation, 2021)
Abstract: This discussion aims to increase understanding of the driving teacher who is part of the education reform process towards a better change and has a fundamental role in implementing independent learning. The ambitious teacher is a program of identifying and training future educational leaders. Motivating teachers are required to have more capabilities than teachers in general. A Motivating Teacher must have the characteristics of a good teacher, but a good teacher is not necessarily a Motivator. A good teacher is a teacher with good performance but only in the classroom. They can improve student achievement, teach creatively and innovatively, and develop their competence. Meanwhile, the role of the driving teacher is not only limited to being successful in managing the class they are teaching. In addition to being a good teacher, a Motivating Teacher must also have the will to lead, innovate, and make changes. As a teacher, the teacher must still integrate character values ​​into the learning process, whether it is included in teaching materials, assignments or daily tests. We always communicate with students in various teaching applications such as WhatsApp links, Google Classroom, Zoom Meeting, Google Meet, and others in teaching and learning activities. There are things to communicate that may be considered trivial and usually happen. Still, it turns out to be very important for us to cultivate good character for students when we talk in online media. Motivating teachers are expected to encourage student growth holistically and become Pancasila students. The driving teacher will be an inspiration for other teachers, have teaching innovations and varied teaching media, and become peer tutors at school.